PATOFISIOLOGI DAN PENATALAKSANAAN NEFROPATI RADIOKONTRAS - Sanjaya, Surya; Suwitra, Ketut (journal of internal medicine, 2012)
Contrast induced nephropaty (CIN) was recognized as one of the leading causes of acute renal failure in patient with renal insufficiency, diabetes mellitus, volume depletion and low cardiac out put. The incidence of CIN is estimated to be 1 Ð 2% in the general population, but the relative risk is greatly increased in diabetics, the elderly, and those with intrinsic renal disease, congestive heart failure, and dehydration. CIN is defined by an increase in creatinine 0.5 mg/dL or 25% from baseline that occurs 2 Ð 3 days after contrast administration. A reduction in renal perfusion caused by a direct effect ofcontrastmedia on the kidney and toxic effects on the tubularcells are generally accepted as the main factors in the pathophysiologyof contrastmedium induced nephropathy. Pathological changes induced by contrastmedium are epithelialcell vacuolization, interstitial inflammation and cellular necrosissuggest a direct toxic effect of contrastmedia on renal tubularepithelial cells. Several measures have been recommended to prevent contrastinduced nephropathy,which include: volume expansion, hydrationwith intravenous administration of normal saline, infusion of mannitol, theophylline, dopamine,acetylcysteine, use of iso-osmolar non-ionic contrastmedia insteadof low-osmolarnon-ionic or high-osmolar ionic contrast,haemofiltration rapidly after contrast administration, injectionof small volume of contrast medium, gadolinium based contrastmedia
Keywords: contrast induced nephropathy